Parasite-specific antibody responses of ruminants infected with Trypanosoma vivax - Vos, G.J.; Gardiner, Peter R. (Cambridge University Press, 1990)
Sera from goats and cattle that were infected with 2 T. vivax clones (ILDat 1.2 and ILDat 2.1) derived from different stocks were analysed for antibody activity against the variable surface glycoproteins (VSGs) of the infecting clones by ELISA and immune lysis. To obtain purified VSG, lysed trypanosomes were separated on dodecyl sulphate-polyacrylamide gels. The gels were copper stained and the VSG protein band was excised from the gel. After destaining, the proteins were electroeluted from the gel slices and used as antigens in ELISA. High titres of IgM and IgG1 antibodies and lytic antibodies against the VSG of the infecting clone were detected. The IgG1 response appeared about 4 days later than the IgM response. IgG2 antibodies were only detected in goats and cattle that were infected with ILDat 1.2. Two goats and 2 calves that were infected with ILDat 1.2 showed recurrent peaks in lytic activity and of IgM and IgG1 antibody activity to the VSG of the infecting variable antigenic type (VAT). Two goats that were infected with ILDat 2.1 showed a similar pattern, but in 2 other goats there was a recurrent peak only in the IgM class. Recurrent peaks of antibody activity to the VSG of ILDat 1.2 and ILDat 2.1 were not detected in the sera of goats that had been inoculated with irradiated trypanosomes or that had been infected with an unrelated T. vivax clone. The recurrence of antibody peaks against the VSG of infection VATs suggests that trypanosomes with completely or partially identical surface determinants reappear during T. vivax infection of ruminants.